Optimization of Land Certificates Through Tax Settlement in the PTSL Program in Central Maluku - Roulinta Y Sinaga; Sarah Selfina Kuahaty; Sri Rumada Sihite; Risqi Mumpuni Dyastuti; Teng Berlianty (Jurnal Ilmiah Dunia Hukum, 2025)
This study analyzes the effectiveness of these mechanisms in supporting land certification optimization in Central Maluku Regency. Using an empirical juridical approach, the research combines legal analysis with field data from interviews and document studies. Findings indicate that obstacles to tax settlement include unclear tax calculations, limited public understanding of taxes beyond Land and Building Tax (PBB), low-income community conditions, difficulties with online payments, and discrepancies between tax data and SPPT. Despite these challenges, PPh and BPHTB settlement can be carried out through two main mechanisms: payment at the Tax Office (KPP) or the Regional Revenue Office (Dispenda) according to applicable formulas. Once taxes are validated and registered at the land office, land certificates can be issued and utilized for economic purposes. Beyond serving as proof of ownership, land certificates can act as collateral for financing, enabling owners to improve productivity and access economic opportunities. Overall, land certification not only provides individual benefits but also contributes to economic stability and sustainable development.